Translation techniques in voiced-over multilingual feature movies - Sepielak, Katarzyna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This paper maps out the use of translation techniques used for multilingual interactions in voiced-over movies. First, the present study aims to determine how multilingual elements are introduced into the films and what implications these elements carry. Secondly, qualitative analysis is used in view of showing which particular translation techniques are employed to transfer multilingual elements in voiced-over translation. Four multilingual movies available with Polish voiced-over soundtrack on DVD were selected: Vicky Cristina Barcelona (directed by Woody Allen, 2008), Nine (Rob Marshall, 2009), Avatar (James Cameron, 2009), and Inglourious Basterds (Quentin Tarantino, 2009). The analysis enabled us to distinguish a type of translation technique which has never been described before: exposition, which in the case of multilingual movies might constitute an efficient tool for recreating the presence of multilingual environment. The results also reveal that translation techniques used to translate multilingual elements do not significantly differ from those used when approaching L1 (main language of the source text) elements. However, the effect they can have on multilingualism might be completely different from that intended when translating L1.